Effective examination for obtaining relation T=f(vc) - Vasilko, Karol (Manufacturing Technology Journal, 2012)
In the development of new cutting materials as well as the application of recent ones it is necessary to know the dependence of their durability on cutting speed. Cutting speed, which determines maximum tool durability, can be derived from it. Recent methodology of finding out this dependence is based mainly on long-term machining examinations and tests, which are demanding on time and material and they can be realised only in laboratory conditions. The paper presents a suggestion of short-term, but equally precise examination, which is based on the observation of tool wear depending on cutting speed.
Keywords: machining; cutting speed; tool durability